2021
DOI: 10.1093/jamia/ocaa326
|View full text |Cite
|
Sign up to set email alerts
|

The risk of racial bias while tracking influenza-related content on social media using machine learning

Abstract: Objective Machine learning is used to understand and track influenza-related content on social media. Because these systems are used at scale, they have the potential to adversely impact the people they are built to help. In this study, we explore the biases of different machine learning methods for the specific task of detecting influenza-related content. We compare the performance of each model on tweets written in Standard American English (SAE) vs African American English (AAE). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Namely, the likelihood of segregation in networks, an effect known as filter bubble [32,34], and the ranking signals that govern how message contents become available to users in a network [3,21,29]. Other issues have been identified derived from online recruitment, especifically participant retention [28], age bias [17] and racial and economical bias [19,31,50]. Some studies have shown that community-based methods, including personal references, local advertisements and pamphlets, indeed recruit more racially diverse samples than other methods [41], and may ensure better chances of participant retention [2,7,44,46,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, the likelihood of segregation in networks, an effect known as filter bubble [32,34], and the ranking signals that govern how message contents become available to users in a network [3,21,29]. Other issues have been identified derived from online recruitment, especifically participant retention [28], age bias [17] and racial and economical bias [19,31,50]. Some studies have shown that community-based methods, including personal references, local advertisements and pamphlets, indeed recruit more racially diverse samples than other methods [41], and may ensure better chances of participant retention [2,7,44,46,49].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, differences in age have be found between participants recruited via social networks * E-mail: alvaropastor@uoc.edu and other methods [17]. As well as a risk for racial and economical bias has been reported when using social networks data [19,31,50]. Moreover, the literature from a diversity of disciplines, including machine learning and data mining [6,23,36], and marketing [20,27,48], sheds light on the various management layers that aim to optimise links between users and the flow of messages.…”
Section: But How Do Social Network Work?mentioning
confidence: 99%
“…Machine learning starts with raw data harvested from an ever-growing collection of data sources. Electronic health records, administrative health records, data warehouses, social media data, 6 as well as population health data are collected and stored with various entities. 7 If the raw data available for training and validation is biased, the analytical results will be biased.…”
Section: Raw Data Can Be Racially Biasedmentioning
confidence: 99%
“…As a characteristic example, models trained to predict intelligence [ 16 , 17 ] might provide a statistically significant predictive performance by picking up solely on age-related variance [ 18 , 19 ]. Moreover, various types of systematic sampling bias, as well as stochastic group differences in the training sample, can result in confounded models (e.g., racially biased machine learning models [ 6 , 20 , 21 ]).…”
Section: Introductionmentioning
confidence: 99%